An evaluation of physician predictions of discharge on a general medicine service. Issue 12 (5th October 2015) - Sullivan, Brian; Ming, David; Boggan, Joel C.; Schulteis, Ryan D.; Thomas, Samantha; Choi, Josh; Bae, Jonathan
Abstract : The goal of this study was to evaluate general medicine physicians' ability to predict hospital discharge. We prospectively asked study subjects to predict whether each patient under their care would be discharged on the next day, on the same day, or neither. Discharge predictions were recorded at 3 time points: mornings (7–9am ), midday (12–2pm ), or afternoons (5–7pm ), for a total of 2641 predictions. For predictions of next‐day discharge, the sensitivity (SN) and positive predictive value (PPV) were lowest in the morning (27% and 33%, respectively), but increased by the afternoon (SN 67%, PPV 69%). Similarly, for same‐day discharge predictions, SN and PPV were highest at midday (88% and 79%, respectively). We found that although physicians have difficulty predicting next‐day discharges in the morning prior to the day of expected discharge, their ability to correctly predict discharges continually improved as the time to actual discharge decreased. Journal of Hospital Medicine 2015;10:808–810. © 2015 Society of Hospital Medicine